ANALYSIS OF CONSIDERATIONS IN CSR ASPECT TOWARDS INCENTIVE TAX OF PT MASPION III IN SIDOARJO JAWA TIMUR (An Empirical Study of CSR at PT. Maspion III Sidoarjo) - Adi, Bayu; Miradji, Moh Afrizal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
CSR has developed into part of the company's business strategy, mainly related to the functions of marketing, public relations, and investment-decision making (Subagyo, 2018). PT. Maspion III in CSR activities has developed into a part of the company's business strategy. in the taxation aspect at PT. Maspion III is one of the important factors that is considered by an organization in designing its CSR program to produce CSR programs that can add business value as well as tax favorable. Whereas on the other hand Maspion III spent funds for its CSR program based on Act Number 36 of 2008 which has regulated the treatment of Income Taxes on expenses or costs incurred in the context of Corporate Social Responsibility (CSR). Provisions regarding this matter are regulated in Article 6 paragraph (1) letters I, j, k, l, and m, in which it is stressed that the amount of taxable income for permanent establishment of permanent establishment), which in fact is reduced in Article 1 PP 93 of the year 2010, for the expenditure of Corporate Social Responsibility (CSR) which can be deducted by a certain%. While for PT. Maspion III for its CSR Program exceeds the provisions of 5%. Therefore, to be able to produce CSR programs that can produce business value programs as well as tax favorable, it is better if the taxpayer considers the taxation aspects when designing his CSR program. Keywords: CSR Aspect Considerations, CSR Tax Incentives, CSR draft, Law